Implications of the Import Ban of Used Clothes Based on Regulation of the Minister of Trade No. 18 of 2021 - Dede Prasetia; Irwansyah Irwansyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The ban on the import of used clothing has significant implications for various aspects, including increasing business opportunities for the local fashion industry, encouraging the development of local raw materials, reducing the volume of textile waste, and increasing the quality of local fashion products. The purpose of this research is to find out what the implications are. the ban on the import of used clothes based on the Minister of Trade Regulation No. 18 of 2021, the research method used is a conceptual approach. The method used in this study is a conceptual approach related to imported data at the central statistical agency with qualitative analysis using the interview method. So, if you look at the results of the discussion above. we can conclude that imported used clothing has a fungus that is dangerous and can transmit disease. And also, this ban has no effect on distributors because they are still supplying imported used clothes domestically. And as for the obstacles themselves, Medan Belawan Customs and Excise has no problems, it’s just that it is not focused on the rat port which is managed by the local government.